(untitled) - Gill, Ranjit (Singapore, 1998)
Never in our economic history have we encountered the economic and financial turbulence and uncertainty that has permeated the last haft of 1997 and which continues with uncertainty in the first quarter of 1998....
Keywords: Foreign exchange,Ngoại hối; Đông Nam Á; Southeast Asia